Cardiac Arrest Risk During Acute Infections: Systemic Inflammation Directly Prolongs QTc Interval via Cytokine-Mediated Effects on Potassium Channel Expression. (August 2020) - Lazzerini, Pietro Enea; Acampa, Maurizio; Laghi-Pasini, Franco; Bertolozzi, Iacopo; Finizola, Francesco; Vanni, Francesca; Natale, Mariarita; Bisogno, Stefania; Cevenini, Gabriele; Cartocci, Alessandra; Giabbani, Beatrice; Migliacci, Nicola; et al.
Abstract : Background: During acute infections, the risk of malignant ventricular arrhythmias is increased, partly because of a higher propensity to develop QTc prolongation. Although it is generally believed that QTc changes almost exclusively result from concomitant treatment with QT-prolonging antimicrobials, direct effects of inflammatory cytokines on ventricular repolarization are increasingly recognized. We hypothesized that systemic inflammation per se can significantly prolong QTc during acute infections, via cytokine-mediated changes in K + channel expression. Methods: We evaluated (1) the frequency of QTc prolongation and its association with inflammatory markers, in patients with different types of acute infections, during active disease and remission; (2) the prevalence of acute infections in a cohort of consecutive patients with Torsades de Pointes; (3) the relationship between K + channel mRNA levels in ventricles and peripheral blood mononuclear cells and their changes in patients with acute infection over time. Results: In patients with acute infections, regardless of concomitant QT-prolonging antimicrobial treatments, QTc was significantly prolonged but rapidly normalized in parallel to CRP (C-reactive protein) and cytokine level reduction. Consistently in the Torsades de Pointes cohort, concomitant acute infections were highly prevalent (30%), despite only a minority (25%) of these cases were treated with QT-prolonging antimicrobials. KCNJ2 K + channel expression in peripheral blood mononuclear cell, which strongly correlated to that in ventricles, inversely associated to CRP and IL (interleukin)-1 changes in acute infection patients. Conclusions: During acute infections, systemic inflammation rapidly induces cytokine-mediated ventricular electrical remodeling and significant QTc prolongation, regardless concomitant antimicrobial therapy. Although transient, these changes may significantly increase the risk of life-threatening ventricular arrhythmia in these patients. It is timely and warranted to transpose these findings to the current coronavirus disease 2019 (COVID-19) pandemic, in which both increased amounts of circulating cytokines and cardiac arrhythmias are demonstrated along with a frequent concomitant treatment with several QT-prolonging drugs. Abstract : Supplemental Digital Content is available in the text.